Production and characterisation of a monoclonal antibody to a cell-surface, glucomannoprotein constituent of Candida albicans and other pathogenic Candida species - Cassone, A.; Torosantucci, A.; Boccanera, M.; Pellegrini, G.; Palma, C.; Malavasi, F. (Journal of Medical Microbiology, 1988)
Summary A murine monoclonal antibody (MAB AF-1) class IgM was raised to a soluble glucomannoprotein extract (GMP) of Candida albicans. Agglutination and indirect immunofluorescence assays with purified MAB showed that AF-1 was directed against a cell-surface epitope shared by C. albicans serotypes A and B, C. tropicalis, C. guilliermondii and C. viswanathii, but not by C. krusei, C. parapsilosis, C. kefyr (pseudotropicalis) and T. glabrata. Treatment with heat, protease or periodatetreated GMP and with other cell-wall extracts of C. albicans provided evidence that the epitope recognised by MAB AF-1 is carried by the polysaccharide moiety of cell-surface glucomannoprotein molecule(s).